DEVELOPMENT OF PUBLIC INFORMATION MEDIA ABOUT THE BENEFITS OF THE WALIKUKUN PLANT (Schoutenia ovata Korth) - Setyowati, Eni; Agustin, Haslinda Yasti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The Walikukun plant is one of the plants that is characteristic and has local wisdom in Tulungagung. The population of this plant is decreasing and is only scattered around Dadi Temple in the Walikukun Hills. Local people's attention to this plant is also low, because not much is known about the properties or benefits of this plant. Research that discusses this plant is still a bit in-depth into its potential as a plant with medicinal properties. Therefore, there is a need for information media to educate the public regarding the potential benefits of this plant. This information media was developed using the ADDIE model (Analyze, Design, Develop, Implementation and Evaluation). The media developed is a QR Code booklet with the title